ANALISIS WACANA KRITIS TERHADAP KOMUNIKASI PEMERINTAH DI MEDIA SOSIAL: IMPLIKASINYA TERHADAP KEPERCAYAAN PUBLIK DAN GOOD GOVERNANCE - Nunti Sibuea; Ramadha Yanti Parinduri; Mahyudin Situmeang; Roikestina Silaban; Barham Siregar (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: Government communication through social media has become an important instrument in delivering public information and building public trust. However, differences in discourse, language use, and communication strategies may influence public perceptions of government credibility and the implementation of good governance. This study aims to analyze government communication on social media using Critical Discourse Analysis and examine its implications for public trust and good governance. The study employed a qualitative approach with Critical Discourse Analysis as the primary method. Data were collected from government social media content, official statements, and relevant supporting documents. The analysis focused on language patterns, discourse construction, power relations, and the representation of transparency, accountability, and public participation. The findings indicate that government communication on social media reflects ideological perspectives and institutional interests that shape public understanding. Communication characterized by transparency, consistency, and responsiveness tends to strengthen public trust and support the implementation of good governance. Conversely, unclear or one-way communication may reduce public confidence and limit meaningful public engagement. Therefore, effective government communication strategies are essential to promote transparency, accountability, and stronger public trust. Keywords: critical discourse analysis; good governance; government communication; public trust; social media   Abstrak: Komunikasi pemerintah melalui media sosial telah menjadi sarana penting dalam penyampaian informasi publik serta membangun kepercayaan masyarakat. Namun, perbedaan wacana, penggunaan bahasa, dan strategi komunikasi dapat memengaruhi persepsi publik terhadap kredibilitas pemerintah serta penerapan good governance. Penelitian ini bertujuan menganalisis komunikasi pemerintah di media sosial menggunakan Analisis Wacana Kritis serta mengkaji implikasinya terhadap kepercayaan publik dan good governance. Penelitian menggunakan pendekatan kualitatif dengan metode Analisis Wacana Kritis. Data diperoleh dari konten media sosial pemerintah, pernyataan resmi, dan dokumen pendukung yang relevan. Analisis dilakukan terhadap pola bahasa, konstruksi wacana, relasi kekuasaan, serta representasi transparansi, akuntabilitas, dan partisipasi publik. Hasil penelitian menunjukkan bahwa komunikasi pemerintah di media sosial merefleksikan perspektif ideologis dan kepentingan institusi yang membentuk pemahaman masyarakat. Komunikasi yang transparan, konsisten, dan responsif cenderung meningkatkan kepercayaan publik serta mendukung penerapan good governance. Sebaliknya, komunikasi yang kurang jelas dan bersifat satu arah dapat menurunkan kepercayaan masyarakat serta menghambat partisipasi publik. Oleh karena itu, strategi komunikasi pemerintah yang efektif menjadi faktor penting dalam mewujudkan transparansi, akuntabilitas, dan kepercayaan publik. Kata kunci: analisis wacana kritis; good governance; kepercayaan publik; komunikasi pemerintah; media sosial